Effect of organic manure and biofertilizers on early growth and vigour of Swietenia macrophylla King. (Mahogany) - Saini, V.; Behera, L. K.; Malek, S. S. (International Journal of Economic Plants, 2024)
The present investigation was aimed at adopting organic production, promoting forest nurseries for sustainable tree plantation, and exploring Swietenia macrophylla King for timber purposes in present times for local conditions. The experiment was designed to assess the growth and vigour of big-leaf mahogany seedlings amongst various organic manures (FYM, Vermicompost, Neem cake, and Poultry manure) in different combinations with red soil and drenching of various biofertilizers (Azotobacter, Azosprillum, Acetobacter, PSB, Pseudomonas, VAM) in early stages of the nursery in comparison to control (Red soil). Among different organic manure treatments, red soil + poultry manure (2:1) exhibited fair qualitative as well as quantitative responses in growth parameters whereas, the maximum seedling quality index was found in Vermicompost treatment. In another aspect of the study, the results showed the highest growth and vigour were recorded in seedlings drenched with VAM @ 10 ml plant-1.